THEEFFEC~NESSOFTEACBING LEARNING STRATEGIES FOR LISTENING: A THEORETICAL ASSUMPTION - Wakako Kobayashi (Celt: A Journal of Culture, English Language Teaching & Literature, 2008)
Of the four language skills, listening is often considered to be the most crucial for the language learner since listening is a highly interactive skill and many SLA researchers have demonstrated its significant role in language acquisition (Vandergrift 1996). The appropriateness, and effective usage of listening strategies can help learners to facilitate the language process. Oxford (1989) states that there is a relationship between learner's variables and the choice of language learning strategies (LLSs). Therefore, the use of appropriate (LLSs), especially metacognitive strategies are significant to improve and advance learners' listening proficiency because their language level will rise.